GAMBARAN PERILAKU SISWA/I SMA SWASTA GAJAH MADA MEDAN TENTANG LABEL INFORMASI NILAI GIZI PADA PRODUK MAKANAN KEMASAN TAHUN 2017 - Indah Maya Sari Nasution; Albiner Siagian; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Adolescent are the group that started happy eating packaged food or snack with a frequency that often. Most snack consumed contain high salt and calories are certainly not good for the health of adolescent. But it is not supported by good behavior towards the use of nutrition label. Read the nutrition label is very important because it can know the nutrients contained in a food product. It can also limit the intake of sugar, salt, fat per day and limit the intake to stop munching a snack. The purpose of this research was to know the description of behavior of the students at SMA Swasta Gajah Mada Medan about nutrition label on packaged food product. This research was descriptive study with cross sectional design. The sample in this research were all students of class X and XI which amount to 90 students. The research was carried out by giving questionnaire to the students and filled in by the students to know about knowledge, attitude, and action towards nutrition label. Data already collected was presented in the form distribution of frequency table and analyzed descriptively. The results showed that the knowledge of students at SMA Swasta Gajah Mada Medan was the most in good category (62.2%). The attitude of students also more in good category (73,3%) and the action of students was the most in the sufficient category (67,8%). Therefore, it is expected that the Education Service of Medan collaboration with Public Health Service of Medan improve the socialization about the nutrition label and its use through the socialization of messages common nutrition balanced to the age of school children consumer so that the introduction obtained can be applied from an early age and become their habit until adulthood later. Additionally, actions of student in paying of nutrition label need to be enhanced with giving information about nutrition label, how to use it and remind students to always get used pay attention label and nutrition label on product packaged food that can be conveyed by the teacher through subject matter related to food nutrients. Keywords: behavior, senior high school student, nutrition label, packaged food